Java for beginners : your easy guide to JAVA programming - Speake, Matthew (Manning Publications, 2022)
This is the course to take if you have zero Java experience, little to no coding experience at all, and are serious about learning to code in Java. Java is one of the most popular programming languages. It is used for software development, mobile and web applications, cloud and big data projects, the internet of things, artificial intelligence, and much more! Knowing Java will give you a highly-desired skill, perfect for a long-term career with a great salary. We know there are countless Java courses out there. Many of them are packed with extra hours of content that aren't necessary for learning to code. With this beginners course, we stick to the most essential skills so you can learn Java quickly and efficiently. (If you are deciding between this Java for Beginners course and The Absolute Beginner’s Guide to Java, this is the more intensive and comprehensive series.). This video tutorial is streamlined but thorough. It starts with the basics of programming, then shows you how to set up a Java programming environment on your computer and how to begin a new project. Then it covers all the aspects of the Java language that you need to get started on your own coding projects. If your goal is to earn a Java Certificate, this course provides the foundational skills you need to progress to studying and passing the Java Certificate exam. Whether you want to start your programming career as a Java developer; add Java to your skill set to improve your hiring potential; or learn Java to develop your own applications, this is the language and the course for you.